Decreased Steroid Hormone Receptor NR4A2 Expression in Kawasaki Disease Before IVIG Treatment - Huang, Ying-Hsien; Chen, Kuang-Den; Lo, Mao-Hung; Cai, Xin-Yuan; Kuo, Ho-Chang (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is a form of acute febrile coronary vasculitis disease that occurs in children. In general, this disease can be treated with a single high-dose of 2 g/kg intravenous immunoglobulin (IVIG). However, the best timing for administering steroid treatment in acute-stage KD is still a matter of debate. In this study, we recruited 174 participants to survey the transcript levels of steroid hormone receptors in KD patients. The chip studies consisted of 18 KD patients that were analyzed prior to IVIG treatment and at least 3 weeks after IVIG administration, as well as 36 control subjects, using GeneChip® Human Transcriptome Array 2.0. Another cohort consisting of 120 subjects was analyzed to validate real-time quantitative PCR. Our microarray study demonstrated significant downregulated expressions of the mRNA levels of NR1A2, RORA, NR4A1-3, THRA, and PPARD in KD patients compared to the controls. However, these genes increased considerably in KD patients following IVIG treatment. After PCR validation, we only observed decreased NR4A2 mRNA levels in the KD patients compared to those of the controls, which increased after they received IVIG treatment. Our study is the first to report the potential effective utilization of steroid treatment in KD. Prior to IVIG treatment, decreased steroid receptors allowed for the reduced treatment role of steroids. However, after IVIG treatment, increased steroid receptors indicate that steroids are effective as a supplementary treatment for KD.